The Effect of Product Innovation and Customer Relationship Management on Satisfaction Mediated by Purchasing Decisions in the Coffee Shop Industry - Laely, Nur; ., Djunedi; Lidiawawan, Angga Rizka (Journal of Ecohumanism, 2024)
The coffee shop industry faces increasingly fierce competition, where consumers have many choices. To retain and attract customers, coffee shops must continuously develop product innovation and improve customer relationships through Customer Relationship Management (CRM). This study aims to identify the effect of product innovation and CRM on customer satisfaction and understand the role of purchasing decisions as a mediator in this relationship. This research uses a survey method by collecting data from coffee shop customers through questionnaires. The research sample consisted of coffee shop visitors who were active during the research period. The collected data were analyzed using statistical techniques, including regression analysis. The results showed that product innovation has a significant positive impact on customer satisfaction. CRM also has a significant favorable influence on customer satisfaction. Furthermore, purchasing decisions were found to mediate the relationship between product innovation and customer satisfaction, as well as between CRM and customer satisfaction. These findings indicate that coffee shops focusing on developing innovative products and implementing effective CRM strategies can increase customer satisfaction. In addition, purchase decisions are an essential intermediary in linking product innovation, CRM, and customer satisfaction. Therefore, coffee shop management must consider better strategies for integrating product innovation, CRM, and purchase decisions to achieve long-term success in this competitive industry. This research contributes significantly to understanding the factors influencing customer behavior and the strategies coffee shop industry players can use.